ANALISIS FAKTOR-FAKTOR PENERAPAN BUILDING INFORMATION MODELING (BIM) DI PROYEK KONSTRUKSI KOTA AMBON - Arfianti, Arfianti; Sangadji, Fauzan A; Taihuttu, Felix (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2025)
Building Information Modelling (BIM) is one of the significant technological and communication advancements in the construction services industry. BIM represents one of the most promising developments in the construction sector. Using BIM technology, a virtual model of a building, known as a building information model, can be digitally constructed and used for planning, design, construction, and maintenance. According to the Regulation of the Minister of Public Works and Public Housing of the Republic of Indonesia No. 22/PRT/M/2018 concerning the Construction of State Buildings, the application of BIM is mandatory for non-simple Stateok buildings with an area exceeding 2000 m² and more than two floors. Based on this regulation, this study aims to evaluate the factors influencing the implementation of BIM among construction project stakeholders in Ambon City, Indonesia. Data for this research were collected through a survey, including questionnaires and interviews with respondents in the construction industry. The analysis employed descriptive statistical methods, including Central Tendency Measurement, Variability Measurement, and Relative Importance Index (RII). The results indicate that the main factor affecting the implementation of BIM in construction projects in Ambon City is the lack of BIM education or training. Keywords: Building Information Modelling, BIM, Key Factors, BIM Implementation